PENDEKATAN TRAIT AND FACTOR DALAM PENGAMBILAN KEPUTUSAN KARIR - Jayadi Jayadi; Fatimah Setiani; Ayu Fitria (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2019)
Adolescence is a period in which decision making is increased. Decisions taken are decisions that determine their future. When facing a situation like this many teenagers cannot explore their choices. This study aims to address career decision making for students at MA Nurul Ummah Sampit by applying the Trait and Factor approach. This study is a qualitative descriptive research with case study approach. The data collection in this study is using interview and observation method. The results of this study indicate that applying of trait and factor approach successfully overcome difficulties in career decision making. The increase in students' career decision making from the low category becomes a very high category after individual counseling.